Process maturity models: Classification by application sectors and validities studies. Issue 4 (25th March 2019) - Lee, Donghun; Gu, Ja‐Whan; Jung, Ho‐Won
Abstract: A variety of maturity models have been developed and evolved as a tool for assessments/benchmarking and continuous improvements for the past two decades. The rapidly increasing number of maturity models led to problems in locating proper maturity models and identifying model validities. To identify maturity models and their validities as well as a classification of models across industrial sectors, a mapping study was applied to initially retrieved 2381 articles on maturity models published in peer‐reviewed journals between 1993 and June 2015. We identified 194 maturity models from 285 articles using a set of quality assessment steps. Among those maturity models, besides the five partially validated ones, this study also identified 26 maturity models that were empirically tested on the basis of tested hypotheses and associated validity types, such as predictive validity and unidimensionality. Additionally, despite the wide presence of maturity models in most application sectors, validated models were observed only in five sectors, eg, IT, industrials, and general. Practitioners and researchers as well as standard organizations can utilize our results to find out maturity models meeting their needs, to identify their validities, and/or to seek research opportunities.